Clinical factors associated with uterine rupture in type II angular pregnancy: a 10-year single-institution retrospective study - Huang, Bao-You; Cobbinah, Portia; Hu, Hao-Ran; Zhu, Ya-Shi; Yang, Mei-Qin; Ding, Jian-Yi; Xu, Xin-xin; Zhou, Hui-juan; Yin, Bo; Han, Ling-Fei (Frontiers in Medicine, 2025)
ObjectiveTo introduce the classification and focus on retrospectively investigating clinical factors associated with uterine rupture.Materials and methodsWe retrospectively analyzed 222 cases of angular pregnancies from January 2010 and December 2021. The selected cases were classified into two types, type I (n = 19) and type II (n = 199). Additionally, type II cases were further subdivided into the ruptured group (n = 25) and the unruptured group (n = 174). Clinical data were collected, and univariate and multivariate analyses were performed to identify significant indicators.ResultsThe mean maternal age was 31.5 ± 5.8 years, with a mean BMI (body mass index) of 22.0 ± 3.2 kg/m2 in 199 type II patients. Spontaneous uterine rupture occurred in 25 (12.6%) patients, while 174 (87.4%) remained unruptured. Univariate analysis revealed that abdominal pain (P < 0.001), a history of previous ipsilateral salpingectomy (P = 0.002), vaginal bleeding (P = 0.005), and gestational age (GA) ≥ 7 weeks (P = 0.044) were significant factors of rupture in type II angular pregnancy. Multivariate analysis identified abdominal pain (OR = 10.410, 95% CI: 3.286–32.977, P < 0.000) and ipsilateral salpingectomy (OR = 3.270, 95% CI: 1.209–8.847, P = 0.020) as statistically significant independent risk factors. The ruptured group had clinically and statistically significant lower hemoglobin and higher transfusion rates.ConclusionThe classification system of angular pregnancy (AP) is a valuable tool that facilitates appropriate management and good prognostic outcomes. Type I angular pregnancy can be followed up till term. Type II angular pregnancy is a high-risk form, and clinicians must carefully assess and investigate other factors such as the history of ipsilateral salpingectomy and abdominal pain and high alert for uterine rupture.